Electrolyte additive and preparation method thereof, electrolyte and battery
By adding electrolyte additives with specific functional groups and intramolecular hydrogen bonds to the electrolyte, the problem of decomposing and producing HF at high temperatures is solved, and the stability of the battery is improved and the cycle life is extended.
Patent Information
- Application Number
- CN202411980207.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The existing electrolyte is easy to decompose under high temperature conditions, producing acidic substances such as HF, resulting in a rapid decline in battery circulation performance and it is difficult to effectively reduce the content of HF.
An electrolyte additive is adopted, whose functional groups can react with HF, reduce the HF content in the electrolyte, and improve the stability of the additive at high temperatures through intramolecular hydrogen bonds, while forming a protective layer on the surface of the positive electrode to inhibit the corrosion of the positive electrode material by HF.
Effectively reduce the content of HF in the electrolyte, improve the stable performance of the battery at high temperatures, extend the battery cycle life, and inhibit the corrosion of the positive electrode material.
Smart Images

Figure CN119798294A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrolytes, and in particular to an electrolyte additive and a preparation method thereof, an electrolyte, and a battery. Background Art
[0002] At present, the market has higher and higher requirements for the performance of electrolytes, and power batteries are developing in the direction of long cycle, high voltage, and high temperature. In actual application, the battery cell often works at a relatively high temperature. Lithium hexafluorophosphate is easy to react with trace amounts of water in the electrolyte under high temperature conditions, decomposing to produce acidic substances such as Lewis acid and hydrofluoric acid (HF). Acidic substances such as HF will in turn promote the further decomposition of lithium hexafluorophosphate. At the same time, acidic substances such as HF will also attack the positive electrode interface, causing the dissolution of transition metal ions in the positive electrode, catalyzing the decomposition of the electrolyte, and ultimately causing the battery cycle performance to decay rapidly. The lithium salt and solvent fluoroethylene carbonate (FEC) in the battery electrolyte are easy to produce gas and decompose at high temperatures, and are easy to produce acidic substances such as Lewis acid and hydrofluoric acid (HF), resulting in a rapid decline in battery cycle performance.
[0003] Therefore, how to effectively reduce the HF content in the electrolyte and improve the stability of the additive at high temperatures is a technical problem that needs to be solved urgently in this field. Summary of the invention
[0004] In view of this, the present application provides an electrolyte additive, the functional group of which can react with HF to reduce the HF content in the electrolyte; the stability of the additive at high temperature can be improved under the action of intramolecular hydrogen bonds; and at the same time, the problems of poor high-temperature cycle performance and easy gas production at high temperature during the use of the battery can be effectively alleviated.
[0005] The present application provides an electrolyte additive having a structure of Formula 1 or Formula 2:
[0006]
[0007] The electrolyte additive can form a protective layer on the positive electrode surface, effectively inhibiting the corrosion of HF in the electrolyte to the positive electrode material and the dissolution of transition metals in the positive electrode material during circulation. The lone pair of electrons on the N element in the isoindole structure can be complexed with the high-valent transition metal ions on the positive electrode surface, inhibiting their dissolution under high pressure, and further improving the battery cycle life; the boron oxygen bond has a strong polarity and a strong electrophilic property, and is easy to react with acid or water to remove water and acid in the electrolyte, thereby stabilizing the electrolyte; the electrolyte additive can also form intramolecular hydrogen bonds, making the molecule more stable at high temperatures. In the electrolyte additives of the structure of Formula 1 or Formula 2, the dotted line means that the hydrogen atoms of the methyl group form intramolecular hydrogen bonds with the oxygen atoms.
[0008] The present application also provides a method for preparing an electrolyte additive, comprising:
[0009] a) reacting isoindoline or 1,2,3,5,6,7-hexahydropyrrolo[3,4-f]isoindole with sodium hypochlorite to obtain intermediate a;
[0010] b) mixing intermediate a, methylmagnesium bromide and trimethylborate to react to obtain intermediate b;
[0011] c) reacting the intermediate b with 1-fluoro-2-(trifluoromethanesulfonyl)benzene to obtain the intermediate c;
[0012] d) The intermediate c, hexamethyldisilazane and boric acid are mixed and reacted to obtain an electrolyte additive.
[0013] The present invention uses isoindoline or 1,2,3,5,6,7-hexahydropyrrolo[3,4-f]isoindole as raw materials, wherein the isoindoline structural formula is The structural formula of 1,2,3,5,6,7-hexahydropyrrolo[3,4-f]isoindole is Isoindoline or 1,2,3,5,6,7-hexahydropyrrolo[3,4-f]isoindole is first reacted with sodium hypochlorite to obtain intermediate a.
[0014] In some specific implementations, the reaction is carried out under alkaline conditions, and the reaction solution can be adjusted to 10-12 using a sodium hydroxide solution, the concentration of which is 0.5M to 1M. In some specific implementations, the reaction time in step a is 4h to 6h, the reaction in step a is carried out at room temperature or under slightly heated conditions, and after the reaction, the intermediate a is filtered and washed to obtain the intermediate a. In some specific implementations, the molar ratio of the isoindoline or 1,2,3,5,6,7-hexahydropyrrolo[3,4-f]isoindole to sodium hypochlorite is 1:(1-6), preferably 1:(3-4).
[0015] In some specific implementations, isoindoline or 1,2,3,5,6,7-hexahydropyrrolo[3,4-f]isoindole is dissolved in water to form a solution, 0.5M to 1M sodium hydroxide solution is added to the solution, and the pH of the solution is adjusted to 10-12; sodium hypochlorite solution is added under stirring, and the reaction is carried out at room temperature or under slight heating for 4h to 6h. After the reaction is completed, the product is filtered and washed with water or an appropriate solvent to obtain intermediate a.
[0016] Then the present application dissolves the obtained intermediate a in an organic solvent, adds methyl magnesium bromide CH3BrMg at low temperature, and then adds trimethyl borate at low temperature to react to obtain intermediate b.
[0017] In some specific implementations, the reaction temperature is -5°C to 5°C, the reaction time is 5h to 6h, the organic solvent includes ether and / or tetrahydrofuran, and the low temperature is -5°C to 5°C. In some specific implementations, the reaction is followed by acidification, separation, washing, and drying to obtain the intermediate b, and the organic layer is dried over anhydrous sodium sulfate, separated, and purified. In some specific implementations, the molar ratio of the intermediate a, methylmagnesium bromide, and trimethylborate is 1:(1-4):(1-4), preferably 1:(2-3):(2-3).
[0018] In some specific implementations, in an anhydrous and oxygen-free atmosphere, the intermediate a is dissolved in an organic solvent, the temperature is lowered to -5°C to 5°C, the pre-prepared methylmagnesium bromide is slowly added, the temperature is maintained low, trimethylborate is slowly added, and the reaction is carried out for 5h to 6h until the reaction is completed. The mixture after the reaction is gradually added to dilute hydrochloric acid for acidification, the liquids are separated, washed, and dried using anhydrous sodium sulfate to obtain the intermediate b.
[0019] Then, the present application dissolves the obtained intermediate b and 1-fluoro-2-(trifluoromethanesulfonyl)benzene in acetophenone to react and obtain intermediate c.
[0020] In some specific implementations, the reaction is carried out under the condition of a catalyst, and the catalyst includes ferric chloride. Using ferric chloride as a catalyst to catalyze the reaction can effectively improve the rate of the reaction, and iron powder can also be added at the same time to maintain the activity of ferric chloride, the amount of ferric chloride is 0.5% to 1% of the total mass of the raw material, and the amount of iron powder is 0.2% to 0.35% of the total mass of the raw material. In some specific implementations, the temperature of the reaction is 60°C to 80°C. In some specific implementations, the molar ratio of the intermediate b to 1-fluoro-2-(trifluoromethanesulfonyl)benzene is 1:(1-4), preferably 1:(1-2).
[0021] In some specific implementations, intermediate c and 1-fluoro-2-(trifluoromethanesulfonyl)benzene are dissolved in acetophenone, ferric chloride is added as a catalyst, iron powder is added to maintain the activity of ferric chloride, and the reaction is carried out at 60° C. to 80° C. for 5 h to 6 h to obtain intermediate c.
[0022] Then, the present application mixes the obtained intermediate c, hexamethyldisilazane and boric acid to react and obtain an electrolyte additive.
[0023] In some specific implementations, the reaction is carried out under the condition of trimethylammonium catalysis, and the amount of trimethylammonium is 0.5% to 1% of the total mass of the raw materials. In some specific implementations, the reaction time of step d is 10h to 12h, the reaction temperature is 115°C to 120°C, and the reaction is followed by cooling, filtering, washing, and distillation to obtain an electrolyte additive. In some specific implementations, the molar ratio of the intermediate c, hexamethyldisilazane, and boric acid is 1:(1-6):(2-6), preferably 1:(2-4):(3-4).
[0024] In some specific implementations, hexamethyldisilazane, intermediate c, hexamethyldisilazane and boric acid are reacted at 115°C to 120°C for 10h to 12h under the catalysis of a small amount of trimethylpentylammonium. After the reaction is completed, it is cooled and filtered to remove the solvent and impurities. The solid product is washed with ether to remove impurities and distilled to obtain an electrolyte additive.
[0025] The present application also provides an electrolyte, comprising the above-mentioned electrolyte additive.
[0026] The electrolyte has good compatibility with the positive electrode and the negative electrode, can improve the stability of the electrolyte at high temperature, and enhance the stability performance of the battery.
[0027] The electrolyte comprises, by mass percentage, 5% to 20% lithium salt electrolyte, preferably 8% to 18%, more preferably 12% to 16%, 75% to 90% organic solvent, preferably 78% to 88%, more preferably 80% to 86%, 1% to 3% second additive, preferably 1% to 2%, more preferably 1% to 1.5%, and 0.5% to 3% electrolyte additive, preferably 0.5% to 2%, more preferably 0.5% to 1%.
[0028] In some specific implementations, the lithium salt electrolyte includes but is not limited to any one or more of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl imide), lithium bis(fluorosulfonyl imide), lithium bis(oxalate borate), lithium difluorooxalate borate or lithium difluorobis(oxalate phosphate), preferably lithium hexafluorophosphate, and the present application has no special restrictions on the selection of lithium salt electrolyte. The organic solvent is any one or more of an organic ester solvent, an ether solvent, a sulfone solvent or a nitrile solvent, preferably one or more of propylene carbonate, diethyl carbonate or ethyl methyl carbonate. In some specific implementations, the second additive is selected from vinylene carbonate, ethylene carbonate, propylene carbonate, fluoroethylene carbonate, 1,3-propane sultone, 1,3-propylene sultone, 1,4-butane sultone, 2,4-butane sultone, N-phenylbis(trifluoromethanesulfonyl)imide, phenyl methanesulfonate, hydroquinone difluorosulfonate, methylene disulfonate, 1,3,5-triallyl isocyanurate, hexamethylene disulfonate, One or more of isocyanate, p-phenylene diisocyanate, isocyanoethyl methacrylate, 2,4-toluene diisocyanate, vinyl sulfate, vinyl disulfate, propylene sulfite, triallyl phosphate, tripropargyl phosphate, tris(trimethylsilane)borate, tris(trimethylsilane)phosphate, tris(vinyldimethylsilane)phosphate, propyl diprop-2-ynyl phosphate, ethyl diprop-2-ynyl phosphate or tetramethylmethylene diphosphate.
[0029] In some specific implementations, the method for preparing the electrolyte includes: slowly adding lithium hexafluorophosphate to an organic solvent in an atmosphere with a water oxygen content of ≤0.1 ppm, adding an electrolyte additive and a second additive after complete dissolution, and stirring to obtain an electrolyte.
[0030] The present application also provides a battery, comprising the above-mentioned electrolyte, a positive electrode plate, a negative electrode plate and a separator.
[0031] The preparation method of the positive electrode sheet comprises: mixing a positive electrode material, a conductive agent, a binder and an organic solvent, coating the mixture on an aluminum foil, drying, rolling and cutting the mixture to obtain a positive electrode sheet;
[0032] The preparation method of the negative electrode sheet comprises: mixing a negative electrode material, a conductive agent, a thickener, a binder and water, coating the mixture on a copper foil, drying, rolling and cutting the mixture to obtain a negative electrode sheet.
[0033] In some specific implementations, the positive electrode material is selected from any one of lithium cobalt oxide, lithium manganese oxide, ternary nickel cobalt manganese lithium, lithium nickel manganese oxide, lithium iron phosphate or lithium manganese iron phosphate, preferably ternary nickel cobalt manganese lithium. The electrolyte additive provided in the present application can form a film on the surface of the positive electrode to prevent HF in the electrolyte from corroding the positive electrode. The negative electrode material is selected from any one of artificial graphite, natural graphite, lithium titanate, metallic lithium, silicon-carbon composite material or silicon oxide, preferably artificial graphite. The diaphragm is selected from a polypropylene diaphragm or a polyethylene diaphragm, preferably a polyethylene diaphragm; the charging and discharging voltage of the battery is 3.0V to 4.5V. The organic solvent includes N-methylpyrrolidone. The present application has no special restrictions on the selection of positive electrode materials, negative electrode materials, diaphragms, conductive agents, thickeners, binders, and organic solvents. The conductive agent includes but is not limited to one or more of carbon black, carbon nanotubes, polyaniline or graphene, preferably carbon black; the positive electrode plate binder includes but is not limited to one or more of polyvinylidene fluoride, sodium carboxymethyl cellulose, polyacrylic acid, polyvinyl alcohol or polyurethane, preferably polyvinylidene fluoride; the conductive agent includes but is not limited to one or more of SuperP, carbon nanotubes or polyaniline, preferably SuperP; the thickener includes but is not limited to one or more of sodium carboxymethyl cellulose, polyvinyl alcohol or polyacrylamide, preferably sodium carboxymethyl cellulose; the negative electrode plate binder includes but is not limited to one or more of styrene-butadiene rubber, polyacrylic acid or polyvinyl alcohol, preferably styrene-butadiene rubber. The diaphragm includes but is not limited to a polyethylene diaphragm coated with a nano-alumina coating, which can be purchased from the market or synthesized by itself, and the synthesis method includes: one of a solution casting method, a melt stretching method, a solvent impregnation method, an electrospinning method or a biaxial stretching method.
[0034] In some specific implementations, the mass ratio of the positive electrode material, the conductive agent, and the binder is (94-97):(1-3):(1-3), preferably (96-97):(1-2):(1-2); the mass ratio of the negative electrode material, the conductive agent, the thickener, and the binder is (92-96):(1-3):(1-3):(2-4), preferably (94-96):(1-2):(1-2):(2-3).
[0035] The present application first mixes the positive electrode material, the conductive agent, and the binder, adds N-methylpyrrolidone (NMP), uses a vacuum defoamer to homogenize to obtain a positive electrode slurry, and evenly coats the positive electrode slurry on an aluminum foil, and after drying, rolling, and cutting, obtains a positive electrode sheet; the negative electrode material, the conductive agent, the thickener, and the binder are mixed, deionized water is added, and the negative electrode slurry is obtained by using a vacuum defoamer, and evenly coated on a copper foil, and after drying, rolling, and cutting, obtains a negative electrode sheet. In some specific implementations, the N / P ratio of the positive and negative electrodes is 1.1.
[0036] The present application then removes water from the diaphragm, and produces a soft-pack laminated battery at an ambient dew point of ≤-45°C, stacks the positive electrode sheet, diaphragm, and negative electrode sheet in order, with the positive and negative electrode tabs on the same side, so that the diaphragm is located between the positive electrode sheet and the negative electrode sheet to play an isolating role, and obtains a bare battery cell. The bare battery cell is placed in an aluminum-plastic film outer packaging, vacuum-baked, cooled to 40°C, injected with the prepared electrolyte, and then packaged, high-temperature infiltrated, formed, aged, secondary vacuum packaged, and divided into volumes to obtain a battery. The electrolyte additive prepared in the present application can form a film on the positive electrode to improve the battery cycle performance. In some specific implementations, the vacuum baking time is 10h to 14h, and the vacuum baking temperature is 80°C to 120°C.
[0037] The electrolyte additive provided in the present application has the structure of Formula 1 and Formula 2. The functional group of the electrolyte additive can react with HF to reduce the HF content in the electrolyte, and can also form a film on the surface of the positive electrode to prevent HF in the electrolyte from corroding the positive electrode. Compared with borate and phenyl borate additives, the electrolyte additive provided in the present application can have a higher capacity retention rate and a lower volume expansion rate under high temperature conditions, and the electrolyte additive can form intramolecular hydrogen bonds to improve its stability in high temperature environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The nuclear magnetic hydrogen spectrum of the electrolyte additive provided in Example 1 of the present application;
[0039] Figure 2 This is the nuclear magnetic hydrogen spectrum of the electrolyte additive provided in Example 2 of the present application. DETAILED DESCRIPTION
[0040] It should be understood that the expression "one or more of..." includes each of the items recited after the expression individually and in various different combinations of two or more of the recited items, unless otherwise understood from the context and usage. The expression "and / or" in combination with three or more recited items should be understood to have the same meaning, unless otherwise understood from the context.
[0041] The use of the terms "comprising", "having" or "containing", including their grammatical synonyms, should generally be understood as open and non-restrictive, for example not excluding other unrecited elements or steps, unless otherwise specifically stated or otherwise understood from the context.
[0042] It should be understood that the order of steps or the order in which certain actions are performed is not important as long as the present invention remains operable. In addition, two or more steps or actions may be performed simultaneously.
[0043] The use of any and all examples or exemplary language, such as "for example" or "including", herein is intended only to better illustrate the invention and does not limit the scope of the invention unless otherwise claimed. No language in this specification should be construed as indicating that any non-claimed element is essential to the practice of the invention.
[0044] In addition, the numerical ranges and parameters used to define the present invention are approximate values, and the relevant values in the specific embodiments have been presented as accurately as possible. However, any numerical value inherently inevitably contains standard deviations due to individual test methods. Therefore, unless otherwise expressly stated, it should be understood that all ranges, quantities, values and percentages used in this disclosure are modified by "about". Here, "about" generally means that the actual value is within plus or minus 10%, 5%, 1% or 0.5% of a specific value or range.
[0045] The present invention is further described below in conjunction with the following examples. The protection scope of the present invention is not limited by the following examples.
[0046] Example 1
[0047] Preparation of electrolyte additives:
[0048]
[0049] 20 g (0.1 mol) of isoindoline is dissolved in water, 0.5 M to 1 M sodium hydroxide solution is added to adjust the pH to alkaline (pH 10-12), 350 mL of 1 M sodium hypochlorite solution is added under stirring, and the reaction is carried out at room temperature or under slightly heated conditions for 4 hours, wherein the molar ratio of isoindoline to sodium hypochlorite is 1:3.5, the product is filtered, and washed with water or an appropriate solvent to obtain intermediate a. Under an anhydrous nitrogen atmosphere, add an appropriate amount of anhydrous solvent (such as ether or tetrahydrofuran) and intermediate a to a dry reaction bottle, cool the reaction bottle to 0°C, slowly add 200 mL of 1MCHMgBr (methyl bromide (CHBr) is slowly added to a reaction bottle containing magnesium metal (Mg) and anhydrous ether (such as diethyl ether) solvent, and reacts under heating and stirring conditions), continue stirring at low temperature, slowly add 19.57 grams (0.2 mol) of trimethylborate to the reaction bottle, react at low temperature for 5 hours, the molar ratio of intermediate a, methyl magnesium bromide and trimethylborate is 1:2:2, after the reaction is completed, slowly add dilute hydrochloric acid (HCl) for acidification, separate the mixture into layers with a separatory funnel, separate the organic layer, wash the organic layer with water, and remove acidic impurities. The organic layer was dried over anhydrous sodium sulfate, separated and purified to obtain intermediate b, 21.73 g (0.1 mol) of 1-fluoro-2-(trifluoromethanesulfonyl)benzene was dissolved in acetophenone, the molar ratio of intermediate b to 1-fluoro-2-(trifluoromethanesulfonyl)benzene was 1:1, 0.1 g of ferric chloride (FeCl) was added as a catalyst, 0.04 g of iron powder (Fe) was used to maintain the activity of FeCl, the mixture was heated to 60°C, and finally intermediate c was separated.
[0050] After drying the intermediate c, hexamethyldisilazane is mixed with the intermediate c, and the hexamethyldisilazane and boric acid are reacted at 115°C for 10 hours under the catalysis of a small amount of trimethylammonium pentyl. The molar ratio of the intermediate c, hexamethyldisilazane and boric acid is 1:2:3. After cooling, the solid product is filtered to remove the solvent and unreacted products; the solid product is washed with ether to remove the remaining impurities, and the electrolyte additive is obtained after two distillations, and the structure is shown in Formula 1. The obtained electrolyte additive is subjected to nuclear magnetic resonance analysis, and the nuclear magnetic hydrogen spectrum is as follows Figure 1 shown.
[0051] Example 2
[0052] Preparation of electrolyte additives:
[0053]
[0054] 16.02 g (0.1 M) of 1,2,3,5,6,7-hexahydropyrrolo[3,4-f]isoindole was dissolved in water, and 0.5 M to 1 M sodium hydroxide solution was added to the solution to adjust the pH to alkaline (pH 10-12). Under stirring, 400 mL of 1 M sodium hypochlorite solution was added, and the reaction was kept at room temperature or slightly heated for 4 hours. The molar ratio of 1,2,3,5,6,7-hexahydropyrrolo[3,4-f]isoindole to sodium hypochlorite was 1:4. The product was filtered and washed with water or an appropriate solvent to obtain intermediate a. Under an anhydrous nitrogen atmosphere, add an appropriate amount of anhydrous solvent (such as ether or tetrahydrofuran) and intermediate a to a dry reaction bottle, cool the reaction bottle to the required low temperature of 0°C, slowly add 200 mL of 1M methylmagnesium bromide (CHMgBr), ensure that the reaction system remains at a low temperature, and slowly add 19.57 g (0.2 mol) of trimethylborate to the reaction bottle under continuous stirring. Continue at low temperature for 5 hours. The molar ratio of intermediate a, methylmagnesium bromide and trimethylborate is 1:2:2. Dilute hydrochloric acid (HCl) is gradually added to the reaction mixture. ) is acidified, the mixture is separated into layers using a separatory funnel, the organic layer is separated, the organic layer is washed with water to remove acidic impurities, the organic layer is dried over anhydrous sodium sulfate, and the intermediate b is separated and purified to obtain the intermediate b, 43.5 grams (0.2 mol) of 1-fluoro-2-(trifluoromethanesulfonyl)benzene is dissolved in acetophenone, 0.1 g of ferric chloride (FeCl) is added as a catalyst, 0.04 g of iron powder (Fe) is used to maintain the activity of FeCl, the mixture is heated to 60°C, the molar ratio of intermediate b to 1-fluoro-2-(trifluoromethanesulfonyl)benzene is 1:2, and finally the intermediate c is separated to obtain the intermediate c. After drying the intermediate c, hexamethyldisilazane is mixed with the intermediate c, and the hexamethyldisilazane and boric acid are reacted at 115°C for 10 hours under the catalysis of a small amount of trimethylammonium pentyl. The molar ratio of the intermediate c, hexamethyldisilazane and boric acid is 1:2:3. After cooling, the solid product is filtered to remove the solvent and some impurities; the solid product is washed with ether to remove the remaining impurities, and the electrolyte additive is obtained after two distillations, as shown in Formula 2. The obtained electrolyte additive is subjected to nuclear magnetic resonance analysis, and the nuclear magnetic hydrogen spectrum is shown as follows Figure 2 shown.
[0055] Example 3
[0056] Prepare electrolyte:
[0057] In an argon glove box with a water and oxygen content of ≤0.1ppm, propylene carbonate (PC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) are uniformly mixed in a mass ratio of PC:DEC:EMC=10:25:50 to obtain an organic solvent, and then lithium hexafluorophosphate (LiPF6) is slowly added to the organic solvent. After complete dissolution, 1,3-propane sultone (PS) and the electrolyte additive provided in Example 1 are added. The masses of LiPF6, organic solvent, PS, and the electrolyte additive provided in Example 1 are 13%, 85.5%, 1%, and 0.5% of the total mass of the electrolyte, respectively. After stirring evenly, the electrolyte is obtained.
[0058] Prepare the battery:
[0059] The positive electrode material nickel cobalt manganese lithium (NCM90), the conductive agent carbon black (SuperP), and the binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 96.5:1.5:2, and N-methylpyrrolidone (NMP) is added after mixing to control the theoretical solid content to 55%. The positive electrode slurry is obtained by homogenization using a vacuum defoamer, and the positive electrode slurry is evenly coated on an aluminum foil with a thickness of 17 μm. After drying, rolling, and cutting, a 50 mm×70 mm positive electrode sheet is obtained.
[0060] The negative electrode material artificial graphite, conductive agent SuperP, thickener sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) were mixed in a mass ratio of 95:1:1.5:2.5, and deionized water was added after mixing to control the theoretical solid content to 52%. A vacuum defoamer was used to homogenize the negative electrode slurry, and the negative electrode slurry was evenly coated on a copper foil with a thickness of 17 μm. After drying, rolling, and cutting, a 52 mm × 72 mm negative electrode sheet was obtained, and the N / P ratio of the positive and negative electrodes was 1.1.
[0061] The polyethylene diaphragm coated with nano-alumina (purchased from Enjie New Materials Co., Ltd.) was cut into 55 mm × 75 mm and vacuum-baked at 70°C for 48 h to remove water.
[0062] A soft-pack laminated battery is made at an ambient dew point of ≤-45°C. The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, with the positive and negative electrode tabs on the same side, so that the separator is located between the positive and negative electrode sheets to play an isolating role, and a bare cell is obtained. The bare cell is placed in an aluminum-plastic film outer package, vacuum-baked at 90°C for 12 hours, and then injected with the prepared electrolyte after cooling to below 40°C, followed by packaging, high-temperature infiltration, formation, aging, secondary vacuum packaging, and capacity division to obtain a battery.
[0063] Example 4
[0064] Prepare electrolyte:
[0065] In an argon glove box with a water and oxygen content of ≤0.1ppm, propylene carbonate (PC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC) are uniformly mixed in a mass ratio of PC:DEC:EMC=10:25:50 to obtain an organic solvent, and then lithium hexafluorophosphate (LiPF6) is slowly added to the organic solvent. After complete dissolution, 1,3-propane sultone (PS) and the electrolyte additive provided in Example 2 are added. The masses of LiPF6, organic solvent, PS, and the electrolyte additive provided in Example 1 are 13%, 85.5%, 1%, and 0.5% of the total mass of the electrolyte, respectively. After stirring evenly, electrolyte 2 is obtained.
[0066] Prepare the battery:
[0067] The positive electrode material nickel cobalt manganese lithium (NCM90), the conductive agent carbon black (SuperP), and the binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 96.5:1.5:2, and N-methylpyrrolidone (NMP) is added after mixing to control the theoretical solid content to 55%. The positive electrode slurry is obtained by homogenization using a vacuum defoamer, and the positive electrode slurry is evenly coated on an aluminum foil with a thickness of 17 μm. After drying, rolling, and cutting, a 50 mm × 70 mm positive electrode sheet is obtained.
[0068] The negative electrode material artificial graphite, conductive agent SuperP, thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber (SBR) were mixed in a mass ratio of 95:1:1.5:2.5, and deionized water was added after mixing to control the theoretical solid content to 52%. A vacuum defoamer was used to homogenize the negative electrode slurry, and the negative electrode slurry was evenly coated on a 17 μm thick copper foil. After drying, rolling, and cutting, a 52 mm × 72 mm negative electrode sheet was obtained, and the N / P ratio of the positive and negative electrodes was 1.1.
[0069] The polyethylene diaphragm coated with nano-alumina was cut into 55 mm × 75 mm pieces and vacuum-baked at 70°C for 48 h to remove water.
[0070] A soft-pack laminated battery is made at an ambient dew point of ≤-45°C. The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, with the positive and negative electrode tabs on the same side, so that the separator is located between the positive and negative electrode sheets to play an isolating role, and a bare cell is obtained. The bare cell is placed in an aluminum-plastic film outer package, vacuum-baked at 90°C for 12 hours, and then injected with the prepared electrolyte after cooling to below 40°C, followed by packaging, high-temperature infiltration, formation, aging, secondary vacuum packaging, and capacity division to obtain a battery.
[0071] Example 5
[0072] The difference from Example 3 is that the masses of LiPF6, organic solvent, PS, and electrolyte additive provided in Example 1 are 13%, 85%, 1%, and 1% of the total mass of the electrolyte, respectively.
[0073] Example 6
[0074] The difference from Example 4 is that the masses of LiPF6, organic solvent, PS, and electrolyte additive provided in Example 2 are 13%, 85%, 1%, and 1% of the total mass of the electrolyte, respectively.
[0075] Comparative Example 1
[0076] The difference from Example 3 is that the electrolyte additive provided in Example 1 is not added to the electrolyte, and instead the additive trimethyl borate (TMB) is added, wherein the masses of LiPF6, organic solvent, PS, and trimethyl borate are 13%, 85%, 1%, and 1% of the total mass of the electrolyte, respectively.
[0077] Comparative Example 2
[0078] The difference from Example 3 is that the electrolyte additive provided in Example 1 is not added to the electrolyte, and the additive 3-cyano-5-fluorophenylboric acid (CFBA) is added instead, wherein the masses of LiPF6, organic solvent, PS, and 3-cyano-5-fluorophenylboric acid are 13%, 85%, 1%, and 1% of the total mass of the electrolyte, respectively.
[0079] Comparative Example 3
[0080] The difference from Example 3 is that the electrolyte additive provided in Example 1 is not added to the electrolyte, and instead the additive tri(2-cyanoethyl)borate (TB) is added, wherein the masses of LiPF6, organic solvent, PS, and tri(2-cyanoethyl)borate (TB) are 13%, 85%, 1%, and 1% of the total mass of the electrolyte, respectively.
[0081] Comparative Example 4
[0082] Prepare electrolyte:
[0083] In an argon glove box with a water and oxygen content of ≤0.1ppm, propylene carbonate (PC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) are uniformly mixed in a mass ratio of PC:DEC:EMC=10:25:50 to obtain an organic solvent, and then lithium hexafluorophosphate (LiPF6) is slowly added to the organic solvent. After complete dissolution, 1,3-propane sultone (PS) and isoindoline are added. The masses of LiPF6, organic solvent, PS, and isoindoline are 13%, 85.5%, 1%, and 0.5% of the total mass of the electrolyte, respectively. After stirring evenly, the electrolyte is obtained.
[0084] Prepare the battery:
[0085] The positive electrode material nickel cobalt manganese lithium (NCM90), the conductive agent carbon black (SuperP), and the binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 96.5:1.5:2, and N-methylpyrrolidone (NMP) is added after mixing to control the theoretical solid content to 55%. The positive electrode slurry is obtained by homogenization using a vacuum defoamer, and the positive electrode slurry is evenly coated on an aluminum foil with a thickness of 17 μm. After drying, rolling, and cutting, a 50 mm × 70 mm positive electrode sheet is obtained.
[0086] The negative electrode material artificial graphite, conductive agent SuperP, thickener sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) were mixed in a mass ratio of 95:1:1.5:2.5, and deionized water was added after mixing to control the theoretical solid content to 52%. A vacuum defoamer was used to homogenize the negative electrode slurry, and the negative electrode slurry was evenly coated on a copper foil with a thickness of 17 μm. After drying, rolling, and cutting, a 52 mm × 72 mm negative electrode sheet was obtained, and the N / P ratio of the positive and negative electrodes was 1.1.
[0087] The polyethylene diaphragm coated with nano-alumina was cut into a size of 55 mm × 75 mm and vacuum-baked at 70°C for 48 h to remove water.
[0088] A soft-pack laminated battery is made at an ambient dew point of ≤-45°C. The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, with the positive and negative electrode tabs on the same side, so that the separator is located between the positive and negative electrode sheets to play an isolating role, and a bare cell is obtained. The bare cell is placed in an aluminum-plastic film outer package, vacuum-baked at 90°C for 12 hours, and then injected with the prepared electrolyte after cooling to below 40°C, followed by packaging, high-temperature infiltration, formation, aging, secondary vacuum packaging, and capacity division to obtain a battery.
[0089] The performance test of the batteries provided in Examples 3-6 and Comparative Examples 1-4 was performed, and the test method was as follows:
[0090] Battery room temperature cycle test: Place the battery to be tested in a constant temperature room at an ambient temperature of 25°C for 4 hours, then charge it at a current of 1C and a voltage of 4.2V, constant current and constant voltage until the cut-off current is 0.05C, then discharge it at a constant current of 1C to a voltage of 3V, cycle it for 500 cycles, and record the capacity retention rate. The capacity retention rate of the nth cycle (%) = (the specific capacity of the nth cycle discharge / the specific capacity of the first cycle discharge) × 100%;
[0091] Battery high temperature cycle test: After the prepared soft-pack battery is placed in an explosion-proof test box at an ambient temperature of 45°C for 4 hours, it is charged at a current of 1C and a voltage of 4.2V, and the cut-off current is 0.05C. Then, it is discharged at a constant current of 1C to a voltage of 3V, and the cycle is repeated for 500 cycles. The capacity retention rate is recorded. The capacity retention rate of the nth cycle (%) = (the specific discharge capacity of the nth cycle / the specific discharge capacity of the first cycle) × 100%;
[0092] Battery high temperature storage test: The battery to be tested is charged and discharged at room temperature for 1 week at a current of 1C, with a voltage range of 3-4.2V. The discharge capacity, internal resistance and volume of the first week are recorded. The internal resistance is tested using a battery internal resistance tester, and the volume is tested using the drainage method. Then charge to 4.2V at a constant current and constant voltage of 1C, with a cut-off current of 0.05C, and then place the battery in a constant temperature oven at 60°C for 7 days. After the time is up, take out the battery and cycle it at room temperature for 2 weeks at 1C / 1C, and record the discharge capacity in the first week after high temperature standing, the discharge capacity in the second week, the internal resistance and volume after storage. Calculate the capacity retention rate, capacity recovery rate, internal resistance growth rate and volume expansion rate of the battery after storage according to the following formula:
[0093] Capacity recovery rate = discharge capacity in the first week after high temperature standing / discharge capacity in the first week × 100%;
[0094] Volume expansion rate = (volume after storage - volume in the first week) / volume in the first week × 100%;
[0095] Internal resistance growth rate = (internal resistance after storage - internal resistance in the first week) / internal resistance in the first week × 100%.
[0096] The test results are shown in Table 1.
[0097] Table 1
[0098]
[0099] According to the data in Table 1, the electrolyte additive prepared by the present application can simultaneously ensure a higher capacity retention rate and a lower volume expansion rate in high-temperature storage, and a higher capacity retention rate in normal temperature cycling and high-temperature cycling, compared with borate and phenyl borate additives.
[0100] Test: Take 20g of the electrolytes prepared in Examples 3-6 and Comparative Examples 1-4 respectively in a conical flask, weigh and record as mass m, add 1-2 drops of neutral red methylene blue mixed indicator, use 0.1M triethylamine ultra-dry acetonitrile solution for titration, record the titration volume V of the standard solution, and calculate the acidity of the electrolyte according to the following formula:
[0101] Electrolyte acidity (ppm) = 20.006 × 1000 × V × c / m;
[0102] The remaining electrolyte was placed in a clean and dry aluminum-plastic bottle, sealed and placed in a 60°C oven for three days. The electrolyte was then taken out and the acidity of the electrolyte was measured again according to the above method. The test results are shown in Table 2.
[0103] Table 2
[0104] Acidity before storage / ppm Acidity / ppm after 3 days storage at 60℃ Example 3 8.7 40.7 Example 4 6.5 37.3 Example 5 8.5 38.5 Example 6 5.7 35.1 Comparative Example 1 9.7 75.5 Comparative Example 2 9.7 88.3 Comparative Example 3 9.7 54.7 Comparative Example 4 8.8 55.2
[0105] From the data comparison of Examples 3-6 and Comparative Examples 1-4 in Table 2, it can be seen that the electrolyte additive prepared by the present application can form intramolecular hydrogen bonds, improve its stability at high temperatures, and also has the function of removing water and acid, inhibiting the increase of acidity in the electrolyte at high temperatures, and can also form a film on the positive electrode to improve the battery cycle performance.
[0106] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. An electrolyte additive, characterized in that: Having the structure of Formula 1 or Formula 2:
2. An electrolyte, characterized in that: The electrolyte additive according to claim 1 is included.
3. The electrolyte according to claim 2, characterized in that The composition includes, by mass percentage, 5% to 20% of lithium salt electrolyte, 75% to 90% of organic solvent, 0.5% to 3% of electrolyte additive and 1% to 3% of second additive.
4. The electrolyte according to claim 3, characterized in that The lithium salt electrolyte includes one or more of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate or lithium difluorobis(oxalatophosphate); The organic solvent includes one or more of propylene carbonate, diethyl carbonate or ethyl methyl carbonate; The second additive is selected from one or more of vinylene carbonate, vinyl ethylene carbonate, propylene carbonate, fluoroethylene carbonate, 1,3-propane sultone, 1,3-propylene sultone, 1,4-butane sultone, 2,4-butane sultone, N-phenylbis(trifluoromethanesulfonyl)imide, phenyl methanesulfonate, hydroquinone difluorosulfonate, methylene disulfonate, 1,3,5-triallyl isocyanurate, hexamethylene diisocyanate, p-phenylene diisocyanate, isocyanoethyl methacrylate, 2,4-toluene diisocyanate, vinyl sulfate, vinyl disulfate, propylene sulfite, triallyl phosphate, tripropargyl phosphate, tris(trimethylsilane)borate, tris(trimethylsilane)phosphate, tris(vinyldimethylsilane)phosphate, propyl diprop-2-ynyl phosphate, ethyl diprop-2-ynyl phosphate or tetramethylmethylene diphosphate.
5. A battery, characterized in that: The invention comprises the electrolyte, the positive electrode sheet, the negative electrode sheet and the separator as claimed in any one of claims 2 to 4.
6. The battery according to claim 5, characterized in that In the positive electrode plate, the positive electrode active material is selected from one or more of lithium cobalt oxide, lithium manganese oxide, ternary nickel cobalt manganese lithium, lithium nickel manganese oxide, lithium iron phosphate or lithium manganese iron phosphate.
7. The battery according to claim 5, characterized in that In the negative electrode sheet, the negative electrode active material is selected from one or more of artificial graphite, natural graphite, lithium titanate, metallic lithium, silicon-carbon composite material or silicon oxide; The diaphragm is selected from a polypropylene diaphragm or a polyethylene diaphragm.
8. A method for preparing an electrolyte additive, characterized in that: include: a) reacting isoindoline or 1,2,3,5,6,7-hexahydropyrrolo[3,4-f]isoindole with sodium hypochlorite to obtain intermediate a; b) mixing intermediate a, methylmagnesium bromide and trimethylborate to react to obtain intermediate b; c) reacting the intermediate b with 1-fluoro-2-(trifluoromethanesulfonyl)benzene to obtain the intermediate c; d) The intermediate c, hexamethyldisilazane and boric acid are mixed and reacted to obtain an electrolyte additive.
9. The preparation method according to claim 8, characterized in that: The molar ratio of isoindoline or 1,2,3,5,6,7-hexahydropyrrolo[3,4-f]isoindole to sodium hypochlorite in step a is 1:(1-6); In step b, the molar ratio of intermediate a, methylmagnesium bromide and trimethylborate is 1:(1-4):(1-4); The molar ratio of the intermediate b to 1-fluoro-2-(trifluoromethanesulfonyl)benzene in step c is 1:(1-4); In step d, the molar ratio of the intermediate c, hexamethyldisilazane and boric acid is 1:(1-6):(2-6).
10. The preparation method according to claim 8, characterized in that: The reaction in step a is carried out under alkaline conditions, and the reaction time in step a is 4h to 6h; The reaction in step c is carried out under the condition of a catalyst, and the catalyst includes ferric chloride; the reaction in step d is carried out under the condition of a catalyst, and the catalyst includes trimethylpentyl ammonium.
Citation Information
Patent Citations
High-voltage electrolyte additive, electrolyte and lithium ion battery
CN116247300A
Electrolyte additive and preparation method thereof, electrolyte and lithium ion battery
CN117304098A
Novel sodium salt, electrolyte and sodium ion battery
CN118359651A
Non-aqueous electrolyte and secondary battery
WO2022262232A1
Small molecule inhibitors of KRAS g12d mutant
WO2024233776A1
Cited By
Bio-based electrolyte additive, preparation method and application
CN121460739A